Financial Distress Dan Opini Audit Terkait Going Concern: Moderasi Penerapan Turnaround Strategy - Pupung Purnamasari; Faradissa Abia Nashwa; Devianti Yunita Harahap; Rini Lestari (Universitas Muhammadiyah Malang, 2023)
Purpose: The auditor is responsible for assessing the appropriateness of using the going concern assumption and providing conclusions regarding material uncertainties that cause business continuity to be disrupted. The purpose of this research is to assess the direct and indirect effect of financial distress on the providing of audit opinion related to going concern through the turnaround strategy plan. Methodology/approach: The sample used in this study consisted of 46 energy sector companies listed on the IDX during 2015 – 2019. The hypothesis testing in this study used PLS-SEM. The method used in this research is quantitative method, descriptive statistics with secondary data as a data source. Findings: The results of the study showed that financial distress has a significant direct or indirect effect on the providing of audit opinions related to going concern. Financial distress has a greater influence on the provision of an audit opinion regarding going concern if it is mediated by the management plan. Simultaneously financial distress and turnaround strategy plan are able to explain the audit opinion related to going concern by 66.6%, while the remaining 33.4% is explained by other factors not included in this study. Practical implications: This research proves that the auditor has considered material doubts about the company's financial factors and the plan to implement a turnaround strategy in providing audit opinions related to going concern. Originality/value: Auditor skepticism in providing audit opinions by considering the management turnaround strategy plan.